Exploring the role of the iron sulphur cluster regulator IscR in Yersinia - Brooks, Clair Rose (2021)
Yersinia pseudotuberculosis is an enteropathogen that is transmitted through contaminated food or water and results in self-limiting fever and gastroenteritis. Y. pseudotuberculosis is closely related to Yersinia pestis, the cause of bubonic, pneumonic and septicaemic plague. Despite causing vastly different diseases, virulence and in particular, type three secretion (T3S) as well as biofilm formation, motility, and aggregation are controlled in both species by several interrelated regulatory systems including quorum sensing (QS). The latter depends on an N-acylhomoserine lactone (AHL) system that incorporates two AHL synthases (YpsI and YtbI) and two LuxR-type response regulators (YpsR and YtbR).